2014
DOI: 10.1128/aac.01653-13
|View full text |Cite
|
Sign up to set email alerts
|

Are Vancomycin Trough Concentrations Adequate for Optimal Dosing?

Abstract: eThe current vancomycin therapeutic guidelines recommend the use of only trough concentrations to manage the dosing of adults with Staphylococcus aureus infections. Both vancomycin efficacy and toxicity are likely to be related to the area under the plasma concentration-time curve (AUC). We assembled richly sampled vancomycin pharmacokinetic data from three studies comprising 47 adults with various levels of renal function. With Pmetrics, the nonparametric population modeling package for R, we compared AUCs es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
351
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 325 publications
(390 citation statements)
references
References 36 publications
(59 reference statements)
20
351
1
6
Order By: Relevance
“…This is partly because of evidence showing a poor correlation between established pharmacodynamic (AUC 0 -24 ) target attainment and measured trough concentrations (6,8). Similar to others, a substantial number of our patients achieved an AUC 0 -24 of Ͼ400 despite having vancomycin trough concentrations below guideline recommendations (Յ15 mg/liter) (6). Of note, we observed that clinicians increased the total vancomycin dose prescribed in these patients, resulting in higher exposures and increasing the risk of AKI.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…This is partly because of evidence showing a poor correlation between established pharmacodynamic (AUC 0 -24 ) target attainment and measured trough concentrations (6,8). Similar to others, a substantial number of our patients achieved an AUC 0 -24 of Ͼ400 despite having vancomycin trough concentrations below guideline recommendations (Յ15 mg/liter) (6). Of note, we observed that clinicians increased the total vancomycin dose prescribed in these patients, resulting in higher exposures and increasing the risk of AKI.…”
Section: Discussionsupporting
confidence: 56%
“…However, current dosing regimens and targets (vancomycin trough concentrations) are an area of great controversy with respect to efficacy. This is partly because of evidence showing a poor correlation between established pharmacodynamic (AUC 0 -24 ) target attainment and measured trough concentrations (6,8). Similar to others, a substantial number of our patients achieved an AUC 0 -24 of Ͼ400 despite having vancomycin trough concentrations below guideline recommendations (Յ15 mg/liter) (6).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations